PENERAPAN MODEL CLIS BERBANTUAN LKPD CONCEPT CARTOON SEBAGAI REMEDIASI MISKONSEPSI SISWA SMP PADA MATERI CAHAYA - Anisa Putri Rinjani; Muhammad Nor; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study to find out the effectiveness of learning model CLIS assisted by student worksheet based on cartoon concept to descrease 2nd grade student’s misconception about light concept in SMPN 3 Pariaman trough remedied process. The study method use pre-experimental design with one group pre-test post-test design. A total 32 students were selected as subject. The data collection used 15 item that represent 5 light concepts. Finding revealed the decline of a total student have misconception each concept about 52% and 55% for the decline of a total misconception each student. The effect size of this study attain a hight result d = 1,59. With the result, CLIS method assisted by LKPD Concept Cartoon effective to remedied 2nd grade student’s misconception about light concept in SMPN 3 Pariaman.Key Words : Misconception, Remedied, Children Learning In Science, Light